EFEKTIVITAS PENERIMAAN PAJAK HOTEL TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI KOTA PAREPARE - Rina Ariska; Indrayani (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2023)
The development of the hotel industry will have a direct impact on increasing local revenue. This is a challenge for the Parepare City Government to explore more revenue from the existing hotel tax sector. This research aims to determine the potential for hotel taxes to increase Parepare City's PAD, to find out the factors that influence hotel tax revenues to increase Parepare City's PAD, and to determine efforts to achieve hotel tax results in increasing Parepare City's PAD. The results of this research show that the Parepare City Government has been quite effective in realizing the existing hotel tax revenue budget during 2018-2019 where the realization amount has reached the predetermined target, except that in 2020 it could not be realized due to the Covid-19 pandemic. It's just that in exploring the hotel tax potential, the Parepare City government is still not effective because the existing hotel tax potential is very large when compared with the actual hotel tax revenue that occurs. Keywords: Effectiveness, Hotel Tax, Original Regional Income